Strategi Pengembangan Wisata Kolam Renang Alam Tilanga’ di Kelurahan Sarira Kecamatan Makale Utara Kabupaten Tana Toraja - Efrain Owen Taruk; Abedneigo Carter Rambulangi; Mince Batara (EKOMA : Jurnal Ekonomi, Manajemen, Akuntansi, 2024)
Strategy for developing the Tilanga' Natural Swimming Pool tourist attraction in Sarira sub-district, North Makale District, Tana Toraja Regency." The aim of this research is to analyze the strategy for developing the Tilanga' Natural Swimming Pool tourist attraction. This research method uses qualitative descriptive analysis and SWOT analysis. Data were collected by means of observation, interviews, library studies, documentation with managers and visitors to the Tilanga' Natural Swimming Pool tourist attraction. The results obtained are that the Tilanga' Natural Swimming Pool tourist attraction has very effective strengths so that the strengths of the Tilanga' Natural Swimming Pool tourist attraction can be used as a guide or motivation and take advantage of opportunities that will be faced and also avoid existing weaknesses and threats to increase interest. and visitor trust in tourist attractions.